Status report on Colorado Cooperative Project in Climatology through 30 June 1959 - Schleusener, Richard A., author; Colorado State University, Civil Engineering Section, publisher (Colorado State University. Libraries, 1959)
This report is a summary of progress on the status of the Colorado Cooperative Project in Climatology. Primary emphasis in this project has been to place certain weather data on I.B.M. punched cards. The history of the project is given, and the types of data included in the punched card program are described. A listing of the stations and years for which weather data are punched is included and procedures for processing the data are described. Detailed instructions are given for processing of weather records from individual stations. No analyses of the punched card data have been possible to date.
CER59RAS30.
Keywords: Climatology -- Research -- Colorado